Comparison of arthropod biodiversity between conventional and alley-cropping system in oil palm plantation in relation to microclimatic and vegetation structures - Abdul Mutalib, Mohamad Ashraf (2018)
Oil palm (Elaeis guineensis) is among the most rapidly expanding and cultivated crops due to high global demand for vegetable oils. Large areas of forest have been converted into oil palm plantations to meet the market demand, especially in Southeast Asia. This has caused biodiversity loss and induced climate change. The alley-cropping system has the potential to promote flora and faunal biodiversity, provide natural predation on pests, and improve microclimate features such as air temperature, ground temperature and higher humidity. This study determines the patterns of arthropod biodiversity, arthropod functional groups, vegetation structure and microclimate conditions with different oil palm agricultural practices. It compared arthropod biodiversity, arthropods predators and decomposers using pitfall traps in five alley-cropping treatments (pineapple, bamboo, black pepper, cacao, bactris), where oil palm is intercropped with another species with two monoculture oil palm treatments. We also compared microhabitat quality of vegetation structure such as vegetation cover for grass and nongrass and height for grass and non-grass using 1m x 1m quadrats and 2m x 5m quadrats. We also measure microclimate such as air temperature, relative humidity, light intensity and wind speed and soil conditions such as soil surface temperature, soil pH and soil moisture. A total of 50,155 arthropod individuals were recorded, representing 19 orders and 28 families of which 14 orders belonging to sub-phylum Insecta, three orders from Arachnida (Araneae; Acarinae; Scorpiones) and two orders from Microcoryphia (Chordeumatida; Geophilomorpha). This study found that the number of arthropod orders, families, abundance, and the number of predators and decomposers were significantly greater in alley-cropping farming plots than those in monoculture plots. This study found that the vegetation structure was significantly greater in the alley-cropping system compared to the oil palm monoculture system. Similarly, this study found that the microclimate and soil condition improved significantly in the alleycropping system than in the monoculture oil palm system. Moreover, this study found that black pepper crops and cacao crops were the best crop species to be implemented in the alley-cropping system due to having a lower temperature (33.19°C; 33.27°C), higher humidity (60.53%; 59.02%) and a richer vegetation structure compared to other crops. The findings from this study suggest that the alley-cropping system could become a key management strategy to improve biodiversity conservation, ecosystem services, vegetation structure and microclimate features within oil palm production landscapes. Furthermore, careful selection of crop species for intercropping with oil palm crops is important to aid in the preservation of variation of vegetation structure and improvement of microclimate features in the plantation.